2016
DOI: 10.3109/07357907.2016.1174257
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of the Combination of Bevacizumab, Pertuzumab, and Octreotide LAR for Patients with Advanced Neuroendocrine Cancers

Abstract: Bevacizumab, pertuzumab, and octreotide depot was well-tolerated with a 16% ORR. Results in the well-differentiated carcinoid tumors are thought provoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…A total of 22 phase II trials with ≥20 patients per arm were identified (4 randomized trials and 18 nonrandomized trials; Fig. ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22 phase II trials with ≥20 patients per arm were identified (4 randomized trials and 18 nonrandomized trials; Fig. ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 trials (Ramanathan et al 2001, Kulke et al 2004, Arnold et al 2005, Sun et al 2005, Yao et al 2007, Dahan et al 2009, Rinke et al 2009, Pavel et al 2011, Raymond et al 2011, Chan et al 2012, Meyer et al 2014, Hobday et al 2015, Bendell et al 2016, Strosberg et al 2016 with ≥20 patients per-arm were identified (10 randomized trials and 10 non-randomized trials), as well as four update reports (Yao et al 2013, 2016b, Faivre et al 2016, Rinke et al 2017) ( Fig. 1 and Table 1).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Combination of depot octreotide, bevacizumab, and pertuzumab, a monoclonal antibody inhibiting the dimerization of HER2 with other HER receptors, was evaluated in a phase II clinical trial in patients with advanced well-differentiated NETs and demonstrated an ORR of 16% and a median PFS of 8.2 months [112]. …”
Section: Molecular and Mutation Targeted Therapymentioning
confidence: 99%